Information-Guided Surgery of Intracranial Gliomas: Overview of an Advanced Intraoperative Technology. Issue 4 (22nd December 2012) - Muragaki, Yoshihiro; Chernov, Mikhail; Yoshimitsu, Kitaro; Suzuki, Takashi; Iseki, Hiroshi; Maruyama, Takashi; Tamura, Manabu; Ikuta, Soko; Nitta, Masayuki; Watanabe, Atsushi; Saito, Taiichi; Okamoto, Jun; et al.
Abstract : The objective of this paper is to provide an overview of advanced information-guided surgical management technology of intracranial gliomas implemented in Japan, represented by the Intelligent Operating Theater at the Tokyo Women's Medical University, established in 2000, where more than 1000 patients with various intracranial pathology have received neurosurgical treatment with application of the intraoperative MRI, updated neuronavigation, and advanced neurophysiological and histopathological monitoring. Additionally, a dedicated computer-based system for accumulating, storing, integrating, and analyzing various surgical data was developed, which provided an opportunity for adequate risk management and prediction of the surgical results. Application of these modalities and tools led to significant improvements in both surgical outcome and long-term patients' prognosis. Further technological developments, such as new therapeutic robot, dedicated laser, and high intensity focused ultrasound are currently under investigation. The final goal is to integrate all these devices and systems into comprehensive neurosurgical framework.